2018
DOI: 10.18203/2320-1770.ijrcog20180166
|View full text |Cite
|
Sign up to set email alerts
|

Use of glycosylated HbA1c and random blood sugar as a screening tool for gestational diabetes mellitus in first trimester

Abstract: INTRODUCTIONGestational Diabetes Mellitus (GDM) is defined as any degree of glucose intolerance with onset or first recognition during pregnancy. It is well known that GDM is associated with maternal and fetal morbidity such as polyhydramnios, preeclampsia, operative delivery, macrosomia, shoulder dystocia, intrauterine growth retardation, neonatal hypoglycaemia and perinatal mortality.The prevalence of GDM varies from 3.8% to 21% in various parts of India based on geographic location and diagnostic methods us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Oral glucose tolerance test (OGTT) is an unpleasant test requiring consumption of 75 grams of glucose and delaying gastric discharge, which can cause nausea and vomiting. It is also a time-consuming method that requires overnight fasting before collection of 3 blood samples [ 11 ]. Moreover, an increase in the maternal blood glucose and fetal growth pathway occurs before 24 weeks of gestation, which has not been diagnosed in GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Oral glucose tolerance test (OGTT) is an unpleasant test requiring consumption of 75 grams of glucose and delaying gastric discharge, which can cause nausea and vomiting. It is also a time-consuming method that requires overnight fasting before collection of 3 blood samples [ 11 ]. Moreover, an increase in the maternal blood glucose and fetal growth pathway occurs before 24 weeks of gestation, which has not been diagnosed in GDM.…”
Section: Introductionmentioning
confidence: 99%
“…A classification system has been proposed for diabetes in pregnancy. 13 This is because the presence of preexisting hyperglycemia in pregnancy may produce vascular changes, thus exaggerating adverse pregnancy outcomes.…”
Section: Diabetes In Pregnancymentioning
confidence: 99%
“…Amreen et al got a sensitivity and specificity of 80% and 55.3%, respectively and a positive and negative predictive value of 63.8% and 73.7%, respectively after taking HbA1c value of 5.5%. 13 They concluded that HbA1c is an effective tool to predict GDM.…”
Section: Diagnosismentioning
confidence: 99%
“…[9] Measurement of random glucose and HbA1c levels obviates the need for fasting and has been explored as alternative screening and diagnostic tests. [31] HbA1c, a measurement of the amount of glucose bound to haemoglobin, is currently the gold standard for long-term blood glucose monitoring. However, it is affected by factors such as ethnicity, anaemia, haemodilation or other blood disorders that hamper its accuracy as a diagnostic tool for GDM.…”
Section: Glucosementioning
confidence: 99%
“…However, it is affected by factors such as ethnicity, anaemia, haemodilation or other blood disorders that hamper its accuracy as a diagnostic tool for GDM. [31][32][33] Therefore, although these tests are convenient, fast, simple, inexpensive and can be done at point of care, the results are inconsistent, with low sensitivity and specificity, and have been unsuccessful to date. Other novel strategies investigated in the SA population include the 'breakfast test'-a non-standardised glucose load administered to pregnant women -instead of the OGTT.…”
Section: Glucosementioning
confidence: 99%